Public Service Accountability at the Youth Sports Service, Culture and Tourism of Majene Regency - Hendrawan; Taufik Iksan; Muhammad Yusri (Kirana Publisher (KNPub), 2024)
The purpose of this research is to analyze the Accountability of public services in the Department of Youth Sports, Culture and Tourism of Majene Regency. The type of research used in this research is explanatory research. This research uses data collection techniques in the form of secondary literature studies with qualitative analysis techniques. The end result of this research is a description of the causal context or cause-effect relationship. The results of this research indicate that public service accountability is not yet optimal and needs to be improved in terms of visitor interview results and direct inspection of tourism sector facilities. The author found that tourist facilities such as places of worship, toilets and In addition, the consistency of levies set on each tourist attraction is not optimal, which differs from visitors, and there are still many waste scattered around tourist attractions, disrupting the comfort of visitors.